Geology of the Alice E. breccia pipe and vicinity, New World mining district, Park County, Montana - Cope, Edward L., author; Thompson, Tommy B., advisor; Burns, Lary K., committee member; Winder, D. R., committee member (Colorado State University. Libraries, 1984)
The Alice E. breccia pipe occurs in a one square mile area of the New World mining district, Park County, Montana. Porphyry gold type mineralization-alteration is exposed at many prospects within the study area. Rocks exposed in the vicinity of the breccia pipe consist of Precambrian granite-gneiss, Cambrian sedimentary rocks and Tertiary sub volcanic intrusives. Hydrothermal alteration is widespread throughout the study area. Propylitic, phyllic, and hydrous skarn alteration all occur in the breccia pipe and the rocks in the vicinity of the pipe. The alteration is zoned vertically and laterally about the breccia. Supergene alteration has resulted from the oxidation of pyritic ores enriching gold relative to other metals at the Alice E. mine. Mineralization consisting of vein and replacement types occurs in association with the hydrothermally altered areas. Magnetite, pyrite, chalcopyrite, bornite and sphalerite occur in order of formation. Gold has accompanied the sulfide stage mineralization. Fluid inclusion data indicate that the metals were deposited in veins whose minimum temperatures of formation ranged from 320°C to 447°C within the study area. Boiling occurred in the deepest parts of the exposed system with metals being deposited in and above the zone of boiling. The fluids were highly saline as evidenced by the presence of halite bearing fluid inclusions. The metals were carried in solution as chloride complexes which became unstable at temperatures less than 400°C. Metal paragenesis and zonation within the area can be explained in terms of chloride complexing and cooling of the ore solutions. The pipe contains a collapse breccia that has been modified by the later intrusions of quartz amphibole latite porphyry dikes and a hypothetical stock which intrude the breccia pipe. The mineral deposits of the area are probably related to these intrusions.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Geology -- Montana -- Park County; Geology